Strategi Komunikasi PT. Mustika Ratu dalam Meningkatkan Reputasi Perusahaan - Fransiska Fransiska; Bintang Nurijadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Public relations communication strategy greatly influences the formation and maintenance of a company's reputation. PT. Mustika Ratu is a company that produces cosmetics and herbal medicine. With so many competitors in this modernization era, PT. Mustika Ratu who has a vision to inherit Indonesian culture must adapt to the times to be able to continue to exist among generation Z, one of which is RTD (Ready To Drink) herbal products packaged in UHT (Ultra High Technology). This study aims to understand the public relations communication strategy carried out by PT. Mustika Ratu to build a reputation. The method used in this research is descriptive qualitative. Data collection techniques using interviews and observation. The result of this research is to know the communication strategy of PT. Mustika Ratu goes through 4 stages, namely situation analysis, planning, implementation and evaluation so that the strategies implemented can run efficiently and effectively as expected by the company and have a good reputation in the eyes of stakeholders.